2021
DOI: 10.11591/eei.v10i1.2299
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of air-conditioning and total load diversity in typical residential buildings

Abstract: Electricity consumption by air-conditioners in residential buildings significantly affects the electrical grid. The stability of the grid can be improved by a precise prediction of air-conditioning (AC) variations. Therefore, more information about the electricity usage patterns specifically on AC load is important. This paper aims to determine the consumption patterns of AC and total load through a field measurement of 20 dwellings located in Kuala Lumpur and Selangor. Next, correlation and clustering are emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…During daytime (7:00 am to 9:00 pm) ACs consumed an average of 1 kWh/day and in the night-time, they consumed 5.2 kWh/day. A Malaysian study with 20 dwellings showed AC was almost used for 5 to 6 h per day at the rate of 0.93 kWh/ day during daytime and 3.43 kWh/day during night-time (Hisham et al 2021). To meet this peak demand, especially during night-time and when solar photovoltaic solutions do not help, larger investments in setting up new power plants may be required.…”
Section: Discussionmentioning
confidence: 99%
“…During daytime (7:00 am to 9:00 pm) ACs consumed an average of 1 kWh/day and in the night-time, they consumed 5.2 kWh/day. A Malaysian study with 20 dwellings showed AC was almost used for 5 to 6 h per day at the rate of 0.93 kWh/ day during daytime and 3.43 kWh/day during night-time (Hisham et al 2021). To meet this peak demand, especially during night-time and when solar photovoltaic solutions do not help, larger investments in setting up new power plants may be required.…”
Section: Discussionmentioning
confidence: 99%
“…However, the amount of electricity consumed in households, mainly for air conditioning, was recorded as 70%, 60%, and 36% in the Kingdom of Saudi Arabia, Oman, and the United Arab Emirates, respectively [25][26][27][28]. There is a similar scenario in Malaysia, where the air condition system is also considered to consume among highest amount of energy, accounting for 28 to 46% of the total electricity consumption [29]. Overall, it can be established that electrical power generation expansion needs to increase by approximately 60% to meet the air cooling sector's energy requirements [24].…”
Section: District Cooling System (Dcs)mentioning
confidence: 99%
“…The indiscriminate discharge of GHG emissions owing to excessive fossil fuel consumption aggravated the increasing climate change across the globe [26,27]. Therefore, energy from biomass is considered among the attractive alternative sources of renewable energy that are proficient and capable of fulfilling the ever-growing energy demand [28,29]. Biomass contributed up to 14% of the worldwide renewable energy consumed, with approximately 90% utilized in rural areas [30][31][32].…”
Section: The Use Of Biomass Energy In Dcsmentioning
confidence: 99%
“…Air conditioning system significantly affects the electrical grid by consuming power in residential buildings. Precise prediction of air conditioner variations can improve the stability of the grid [1]. Energy consumption in an air conditioning system is a key area to concentrate on reducing energy consumption to ensure thermal comfort when designing the air conditioning system.…”
Section: Introductionmentioning
confidence: 99%